PROFITABILITY AND LEVERAGE, AND THE IMPLICATION ON THE DIVIDEND POLICY OF JAKARTA ISLAMIC INDEX - Dewantara, Anaz Bima; Siswanto, Siswanto; Rizqi, Achmad Maulana (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2019)
The aim of this study is to analyze the influence of leverage and profitability to dividend policy reinforced by liquidity and cash adequacy. Liquidity and cash sufficiency was assumed as moderation variable. This research used moderated regression analysis. Data obtained from secondary data that is company's financial report registered at Jakarta Islamic Index in period 2012-2016. The results show that profitability and leverage had no effect on dividend policy. Otherwise, liquidity is not able to moderate profitability and leverage to dividend policy. Therefore, cash variable and cash equivalents variable are able to moderate the relationship between ROA and dividend policy, but those can’t moderate ROE, DER, and DAR to dividend policy.